Modelo de pronóstico para las exportaciones del Perú con la comunidad andina de naciones. Enero 1999 - Abril 2007 - Pajuelo Gonzáles, Luis Alfredo (2012)
In this research of longitudinal descriptive type, was raised as a goal: determine a model to forecast exports of Peru, thousands of dollars, with the Andean Community of Nations, from the historical monthly series from January 1999 - April 2007, obtained from the website of the Andean Community, Secretary General, project statistics. The first 96 months data were used for the estimation of the model, and the 4 remaining months for the validation of the model. We found the study series presented a non stationary behavior in mean and variance; to apply the first differentiation, generated estacionariedad in media, but not in variance, so it became necessary to use the model SARIMA (1, 1, 1) (0, 0, 6), that turned out to be right and with validity of prognosis, which estimates exports of the Peru with the Andean Community of Nations with a standard error of estimate of 4625 thousands of dollars per monthan explanation of the model on the export of 70.6%, with a percentage of average absolute error of 9.4 per cent and an average percentage of error - 0.93%; indicating a non biased Outlook and a technique not overestimates or underestimates consistently the Peru exports to the Andean Community of Nations.